Pigment Dispersing Factors and Their Cognate Receptors in a Crustacean Model, With New Insights Into Distinct Neurons and Their Functions - Alexander, Jodi L.; Oliphant, Andrew; Wilcockson, David C.; Brendler-Spaeth, Timothy; Dircksen, Heinrich; Webster, Simon G. (Frontiers in Neuroscience, 2020)
Pigment dispersing factors (PDFs, or PDHs in crustaceans) form a structurally related group of neuropeptides found throughout the Ecdysozoa and were first discovered as pigmentary effector hormones in crustaceans. In insects PDFs fulfil crucial neuromodulatory roles, most notably as output regulators of the circadian system, underscoring their central position in physiological and behavioral organization of arthropods. Intriguingly, decapod crustaceans express multiple isoforms of PDH originating from separate genes, yet their differential functions are still to be determined. Here, we functionally define two PDH receptors in the crab Carcinus maenas and show them to be selectively activated by four PDH isoforms: PDHR 43673 was activated by PDH-1 and PDH-2 at low nanomolar doses whilst PDHR 41189 was activated by PDH-3 and an extended 20 residue e-PDH. Detailed examination of the anatomical distribution of all four peptides and their cognate receptors indicate that they likely perform different functions as secreted hormones and/or neuromodulators, with PDH-1 and its receptor 43673 implicated in an authentic hormonal axis. PDH-2, PDH-3 and e-PDH were limited to non-neurohaemal interneuronal sites in the CNS; PDHR 41189 was largely restricted to the nervous system suggesting a neuromodulatory function. Notably PDH-3 and e-PDH were without chromatophore dispersing activity. This is the first report which functionally defines a PDHR in an endocrine system in a crustacean and to indicate this and other putative roles of this physiologically pivotal peptide group in these organisms. Thus, our findings present opportunities to further examine the endocrine and circadian machinery in this important arthropod phylum.